BALANCING SHIFTS AND MARRIAGE: THE ASSOCIATION BETWEEN WORKLOAD AND MARITAL ROLE CONFLICT AMONG MARRIED FEMALE NURSES - Sherly Argya Putri; Ratriana Yuliastuti Endang Kusumiati (EDUCATIONE, 2026)
Female nurses commonly face dual-role demands from shift-based clinical work and family responsibilities, which can heighten marital role conflict and threaten work–family balance. This study examined the association between perceived workload and marital role conflict among married female nurses at PKU Muhammadiyah Hospital, Temanggung. Using a quantitative correlational design, data were collected from 90 married female nurses selected through proportionate stratified random sampling. Workload was measured with the NASA Task Load Index (NASA–TLX), while marital role conflict was assessed using the Work–Family Conflict Scale developed by Netemeyer et al. (1996). Pearson correlation analysis showed a positive and statistically significant relationship between workload and marital role conflict (r = 0.311; p = 0.003), indicating that higher perceived workload is associated with greater conflict in fulfilling marital and family roles. These findings suggest that workload—particularly in shift-based nursing—may contribute to strain at home through reduced time, energy depletion, and emotional fatigue. The study concludes that hospital management should prioritize more proportional workload allocation and fairer shift arrangements, complemented by supportive programs (e.g., stress management, supervisor support, and work–family facilitation) to protect nurses’ well-being and family functioning. Future research should employ longitudinal or mixed-method designs and test potential mediators/moderators such as job resources, social support, marital satisfaction, and coping strategies.